Komunikasi dan Interaksi Ninik Mamak dengan Anak Kemenakan dalam Pembagian Harta Warisan Masyarakat Lubuk Bendahara Sebagai Wujud Penerapan Restorative Justice - askarial, askarial; Rinaldi, Kasmanto (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2023)
This study aims to analyze how the role of Ninik Mamak in the distribution of inheritance in the Lubuk Bendahara community, as is known, in Lubuk Bendahara Village there is a so-called Ninik Mamak, Ninik Mamak is the elder or the leader of the tribe. Ninik Mamak has various duties not to regulate the distribution of inheritance that occurs in Lubuk Bendahara Village. This study uses a qualitative method with a descriptive approach. There are three stages that are passed in this research, namely observation, interview and documentation. based on the results obtained, namely the settlement of inheritance disputes in Lubuk Bendahara was carried out by involving Ninik Mamak. Ninik Mamak's role in the distribution of inheritance is more inclined to be considered or reduce the inheritance conflicts that occur. In the distribution of inheritance in Lubuk Bendahara, conflicts often arise, especially when left in the form of land, and there are quite a number of children left behind, so that there are often fights between siblings. Ninik Mamak's role here is as a mediator or mediator in the perceived conflict